Metabolic Syndrome Features and Excess Weight Were Inversely Associated with Nut Consumption after 1-Year Follow-Up in the PREDIMED-Plus Study. Issue 12 (23rd October 2020) - Julibert, Alicia; del Mar Bibiloni, Maria; Gallardo-Alfaro, Laura; Abbate, Manuela; Martínez-González, Miguel Á; Salas-Salvadó, Jordi; Corella, Dolores; Fitó, Montse; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Wärnberg, Julia; Vioque, Jesús; et al.
ABSTRACT: Background: High nut consumption has been previously associated with decreased prevalence of metabolic syndrome (MetS) regardless of race and dietary patterns. Objectives: The aim of this study was to assess whether changes in nut consumption over a 1-y follow-up are associated with changes in features of MetS in a middle-aged and older Spanish population at high cardiovascular disease risk. Methods: This prospective 1-y follow-up cohort study, conducted in the framework of the PREvención con DIeta MEDiterránea (PREDIMED)-Plus randomized trial, included 5800 men and women (55–75 y old) with overweight/obesity [BMI (in kg/m 2 ) ≥27 and <40] and MetS. Nut consumption (almonds, pistachios, walnuts, and other nuts) was assessed using data from a validated FFQ. The primary outcome was the change from baseline to 1 y in features of MetS [waist circumference (WC), glycemia, HDL cholesterol, triglyceride (TG), and systolic and diastolic blood pressure] and excess weight (body weight and BMI) according to tertiles of change in nut consumption. Secondary outcomes included changes in dietary and lifestyle characteristics. A generalized linear model was used to compare 1-y changes in features of MetS, weight, dietary intakes, and lifestyle characteristics across tertiles of change in nut consumption. Results: As nut consumption increased, between each tertile there was a significant decrease in WC, TG, systolic blood pressure, weight, and BMI ( P < 0.05), and a significant increase in HDL cholesterol (only in women, P  = 0.044). The interaction effect between time and group was significant for total energy intake ( P < 0.001), adherence to the Mediterranean diet (MedDiet) ( P < 0.001), and nut consumption ( P < 0.001). Across tertiles of increasing nut consumption there was a significant increase in extra virgin olive oil intake and adherence to the MedDiet; change in energy intake, on the other hand, was inversely related to consumption of nuts. Conclusions: Features of MetS and excess weight were inversely associated with nut consumption after a 1-y follow-up in the PREDIMED-Plus study cohort. This trial was registered at isrctn.com as ISRCTN89898870.